E-mobility options for ADB developing member countries. - Grutter, Jurg M. ([Manila] Asian Development Bank, 2019)
This working paper presents an analysis of options for the development and deployment of e-mobility solutions in developing Asian countries. The growing motorization of Asia will not only increase traffic congestion, but it will also increase greenhouse gas emissions. Solving this challenge will require moving away from the combustion engine and toward electric and hybrid vehicles. Recommendations in this paper focus on actions that can be taken to support this evolution of the Asian transport sector.
Keywords: Development economics; Electronic books